Economics of calf grower operations in relation to dairy-sourced day-old calf price and feedlot outcomes - Hunsaker, Jade (My University, 2020)
Holstein steers compose 15% of the U.S. beef supply despite several factors that place Holstein feeders at a disadvantage including higher calf mortality than traditional beef breeds. This study examined how to improve overall profitability via mortality reduction at a calf ranch. Reinvestment of profit margins to increase Holstein survivability, specifically by providing incentive for dairies to improve survivability, is worth further study. A cattle owner’s enterprise budget is constructed that uses ten-year average cash prices for live cattle, feed inputs, and yardage fees. The analysis revealed that financial breakeven occurs at a 13.44% calf mortality at the calf ranch, ceteris paribus. Additionally, for each 1.0% decrease in mortality leads to an increase in profitability by $14.45/head. A sensitivity analysis was conducted and revealed that at 10% mortality, a margin of $79.63 exists that can be reinvested, and $7.42 exists at 15% mortality. The cattle owner may increase profits by incentivizing dairies in multiple ways. A pricing schedule that rewards dairies for directly reducing mortality at the calf ranch over a given time frame is the most direct, but the potential income may be inconsequential to dairies. A model that rewards processes at the dairy such as proper colostrum management and sterilization of the calves’ umbilicus provides more consistent treatment across the multiple sources for bull calves. A third option is to combine bonuses and discounts with education for dairy maternity crews.
Keywords: Calf Price; Feedlot; Agricultural Economics; Profitability; Holstein